Pengeluaran Publik Untuk Kesehatan dan Status Kesehatan di Negara – Negara Asia - Barokatuminalloh Barokatuminalloh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
Health is one of prominent factors of human capital development. Beside its important rule to national wealth measure, health sector has an intrinsic value to extent individual ability and freedom. Also, health sector has instrumental value to income contribution and strengthen body ability. So, health programs, run by government, do not only give benefit individually, but the programs have well impact to surrounding environment also. The purpose of this research is to indicate how government expenditure to health sector, measured by IMR and life expectancy rate at birth to thirteen Asian countries, will be affected by the countries economics conditions. This analysis shows that government expenditure to health sector and health status of the countries people is related positively. It means that the increasing of government expenditure will impact to people health increasing of the country, indicated by decreasing of IMR value and increasing of live expectancy rate. This research shows also that economic conditions of a nation have positive impact to health condition, where the Gross Domestic Product per capita factor positively impacts to IMR decreasing and of life expectancy at birth increasing in the region. So, to extent people wealth, the government role will be the key factor that measured by the capacity of government expenditure to heath sector.Keywords: health sector, IMR, life expectancy at birth